Estimating Willingness to Pay for an Improved Service Delivery to Patients Referring Namazi Hospital Chemical Therapy Ward in Iran Using Contingent Valuation - Kavosi, Zahra (Asian Pac J Cancer Prev, 2018)
OBJECTIVE: The aim of this study was to estimate patients’ willingness to pay (WTP) for improving the quality of non-medical aspect in Namazi hospital patients chemotherapy an assessment using the contingent valuation method (CVM). PATIENTS AND METHODS: This was an applied, cross-sectional and analytical-descriptive study carried out in Iran, Shiraz in 2013. A sample of 185 patients was determined using random sampling. Multiple choice questions and follow-up open-ended questions were employed to elicit patients’ WTP. The question asked patients would have to pay for this improving their own pocket. linear regression were used to Econometrically estimate the maximum WTP using STATA 11 software. RESULTS: The results of this study indicated that 31% were male and 69% were female and the adjusted mean WTP was PPPUS$15 for pat maximum amount of willing to pay was for to get the same quality service in own city respondents (PPPUS$16) and minimum amount of willing to pay was to get advice of experienced nurse(PPPUS$10) Patients were willing to pay more if their satisfaction with two attributes of care were increased. The cancer type and income taking care of you are significant factors influencing a patient’s WTP. CONCLUSIONS: In the worst socio-economic conditions of the people were willing to pay to improve the reducing wait times in receiving a drug and get the same quality service in own city respondents. In Future efforts Health policymakers should consider the ability to pay when making their decision.